Cluster-based improved Malt barley technology demonstration in selected districts of Arsi and West Arsi zones of Oromia Regional State, Ethiopia - Sintayehu Abebe; Lemlem Abebe (Open Journal of Plant Science - Peertechz Publications, 2021)
A total of 5 malt barley clusters which contains 104 hectares of land were formed in collaboration with the districts level experts and "kebeles" level Development Agents (DAs). The Zones were selected due to their potential for Malt barley production.One popular variety called IBON 174/03 was demonstrated along with its full-recommended packages in the study areas.Training were given for a total of 164 participants (135 farmers, 12 DA and 17 experts ) at different stage on production practice of Malt barley techinologies. To raise farmer's awareness on the performance of the Malt barley techinologies, a total of 5 field days were organized, by these field days, a total of 308 participants were attended the field events (261 farmeres, 15 development agents and 23 Experts 9 Higher Officials and Others were attened the events). The variety (IBON 174/03) demonstrated at study districts was acceptable during field visit and field day by farmers due to its disease tolerant, well adaptation and its productivity after harvesting (at all study areas the variety has showed a yield advantage over the Ethiopial national average yield of barley (21 quintals per hectare CSA;2020.